Effects of Cooperative Learning Model Send Greetings and Problems Type Activity and Results of Learning - Kustantini Farah Yogi; Dwi Priyo Utomo; Zuhkrufurrohmah (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
This research is an experimental study whose purpose is to determine whether there is an effect of the cooperative learning model type sending greetings and sending questions on the activities and learning outcomes of vocational students' mathematics. The subjects of this study were students of X-KPW 1 and X-KPW 2 of SMK Muhammadiyah 1 Malang City in the 2020/2021 academic year as many as 20 people in each class. To collect data about mathematics learning activities, students use observation sheets during learning activities and learning outcomes tests are used to determine students' mastery of learning materials. Then the data obtained were analyzed with a quantitative approach. Based on the MANOVA test, the significance value of activity and learning outcomes is 0.000, which means that H0 is rejected. The conclusion is that the cooperative learning model of sending greetings and questions has a significant influence on student activities and learning outcomes there are differences in the average activity and learning outcomes of students using conventional learning.